Desempenho da produção agropecuária dos municípios pertencentes ao Escritório de Desenvolvimento Rural de Andradina, SP, Brasil - Carvalho, Jaqueline Bonfim De; Panosso, Alan Rodrigo; Sabbag, Omar Jorge; Tarsitano, Maria Aparecida Anselmo (Universidade Católica Dom Bosco, 2017)
Abstract: The assignment of the Rural Development Offices (EDR) is execution of activities related to regional plans and municipal rural development. The objective of work was to analyze the agricultural efficiency thirteen municipalities belonging to EDR of Andradina/SP, by multivariate statistics and data envelopment analysis (DEA). The analyzes allowed conclude that most units working inefficiently, with Valparaíso and Bento de Abreu highlight municipalities.

Resúmen: La asignación de las Oficinas de Desarrollo Rural (EDR) es la ejecución de las actividades relacionadas con los planes regionales y municipales de desarrollo rural. El objetivo del trabajo fue analizar la eficiencia agrícola del trece municipios pertenecientes a la EDR Andradina/SP, por estadística multivariante y análisis envolvente de datos (DEA). Los análisis mostraron que la mayoría de las unidades trabaja de manera ineficiente, con Valparaíso y Bento de Abreu como los municipios destacados.

Résumé: La affectation des Bureaux de Développement Rural (EDR) est l'exécution des activités liées aux plans régionaux municipal et le développement rural. L'objectif travail était d'analyser l'efficacité de l'agriculture treize municipalités appartenant à EDR Andradina/SP, par les statistiques multivariées et l'analyse d'enveloppement des données (DEA). Les analyses ont montré que la plupart des unités fonctionne inefficacement, avec Valparaíso et Bento de Abreu comme les municipalités en vedete.

Resumo: A atribuição dos Escritórios de Desenvolvimento Rural (EDR) é execução das atividades relativas aos planos regionais e municipais de desenvolvimento rural. O objetivo do trabalho foi analisar a eficiência agropecuária de treze municípios pertencentes ao EDR de Andradina, SP, através da estatística multivariada e análise envoltória de dados (DEA). As análises permitiram concluir que a maioria das unidades trabalha de maneira ineficiente, tendo Valparaíso e Bento de Abreu como municípios destaque.
Agricultural production performance of municipalities belonging to Rural Development Office Andradina, SP, Brazil
Rendimiento de la producción agrícola de los municipios pertenecientes a la Oficina de Desarrollo Rural Andradina, SP, Brasil
Keywords: grouping; Andradina; agricultural efficiency; multivariate statistics; DEA; agrupamento; Andradina; eficiência agropecuária; estatística multivariada; DEA